Flexible AgNW/PDMS nanocomposite for strain and pressure sensing - Kárason, Halldór; Ritrovato, Pierluigi; Maffulli, Nicola; Tortorella, Francesco; Boccaccini, Aldo R. (Materials Letters, 2024)
This study presents the fabrication and characterization of an ultra-thin (<1 mm) piezoresistive sensor based on a silver nanowire (AgNW) and polydimethylsiloxane (PDMS) nanocomposite, capable of simultaneous strain and pressure sensing. The sensor exhibits high sensitivity, detecting strains as low as 0.5 % with a range of up to 40 %, demonstrates frequency responsiveness from 0.5 to 3 Hz, and maintains functionality over 1000 cycles. The sensor's performance was evaluated through cyclic tensile and compressive tests. We hypothesize that the compression sensing mechanism is a consequence of the Poisson effect in the PDMS substrate, where transverse compression induces axial strains parallel to the AgNW network, causing disconnections within the nanowire matrix. The sensor's versatility was demonstrated through various biofeedback applications, including finger bending, applied pressure, calf raises, and elbow flexion. With its thin profile and dual-mode sensing capability, this AgNW/PDMS nanocomposite sensor shows promise for biomechanics, sports science, and healthcare monitoring applications.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Electronic materials; Nanocomposite; Piezoresistivity; Sensors